2000
DOI: 10.1002/1098-1063(2000)10:4<438::aid-hipo10>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity at hippocampal to prefrontal cortex synapses: Dual roles in working memory and consolidation

Abstract: The involvement of the hippocampus and the prefrontal cortex in cognitive processes and particularly in learning and memory has been known for a long time. However, the specific role of the projection which connects these two structures has remained elusive. The existence of a direct monosynaptic pathway from the ventral CA1 region of the hippocampus and subiculum to specific areas of the prefrontal cortex provides a useful model for conceptualizing the functional operations of hippocampal-prefrontal cortex co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
81
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 33 publications
14
81
1
Order By: Relevance
“…While the functional significance of this GABA-regulation requires further investigation, our results suggest that it is expressed when the HFS also becomes able to produce LTP in the mPFC. Perhaps as suggested earlier, this inhibitory function may serve as an "anti-LTP" or a threshold control mechanism to prevent too much LTP saturating in the mPFC network (Laroche et al, 2000). With a focus on the developmental changes in mPFC, the current study further demonstrates an increase in the dopamine receptors that may play an important role in the maturation of the HFS-induced LTD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While the functional significance of this GABA-regulation requires further investigation, our results suggest that it is expressed when the HFS also becomes able to produce LTP in the mPFC. Perhaps as suggested earlier, this inhibitory function may serve as an "anti-LTP" or a threshold control mechanism to prevent too much LTP saturating in the mPFC network (Laroche et al, 2000). With a focus on the developmental changes in mPFC, the current study further demonstrates an increase in the dopamine receptors that may play an important role in the maturation of the HFS-induced LTD.…”
Section: Discussionsupporting
confidence: 88%
“…The timing when these additional dopamine-mediated inhibitory influences start to appear in the mPFC is close to when HFS-induced LTD is possible. Lastly, the enhanced inhibition following HFS is not inconsistent with the potential increase in excitation that may likely co-exist at a limited set of synapses and can not be detected in the populational responses in the current study (Laroche et al, 2000). The potentially increased glutamate transmission may provide further drive on nearby interneurons and the net effect is a reduction in the populational activity.…”
Section: Discussionsupporting
confidence: 61%
“…Experimental lesions of the DLPFC in primates disrupt performance on delayed response tasks [42][43][44] and DLPFC cells maintain elevated rates of discharge during the delay period of delayed response tasks [45][46][47][48] . Moreover, recent evidence indicates that the PL of rats is homologous to the DLPFC of primates [21] .…”
Section: Discussionmentioning
confidence: 99%
“…inactivation of the ventral mPFC (PL and AC cortices), produces marked deficits in delayedresponse tasks involving short or long delays [13][14][15][16][17][18][19][20] . Recent evidence indicates that the PL cortex is directly involved in limbic/cognitive functions, homologous to the dorsolateral prefrontal cortex (DLPFC) in primates [21] , which is necessary for delayed-response tasks [2,22] . But and understanding the neuronal basis of behavior [23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine acts directly by stimulating nicotinic acetylcholine receptors and also promotes the release of downstream neurotransmitters including dopamine and serotonin (Wonnacott et al, 1989). These nicotinic receptors are located in a variety of brain regions including the prefrontal cortex and the hippocampus, both of which are important for memory function (Goldman-Rakic, 1996;Jarrard, 1993;Laroche et al, 2000). We have shown that nicotinic receptors in the hippocampus are important for memory performance as local hippocampal infusion of nicotinic receptor antagonists significantly impairs memory function (Arthur and Levin, 2002;Bancroft and Levin, 2000;Bettany and Levin, 2001;Felix and Levin, 1997;Kim and Levin, 1996;Levin et al, 2002).…”
Section: Introductionmentioning
confidence: 93%